Cadaveric Penile Prosthesis Workshop training improves surgical confidence levels of urologists: South Asian Society for Sexual Medicine course survey. (9th August 2020) - Krishnappa, Pramod; Srini, Vasan S; Shah, Rupin; Lentz, Aaron C; Garaffa, Giulio; Martinez‐Salamanca, Juan Ignacio; Moncada, Ignacio
Abstract : Objectives: To analyze the impact of South Asia's first cadaveric hands‐on workshop on urologists' training in inflatable penile prosthesis surgery. Methods: A total of 72 urologists/andrologists participated in the 2019 South Asian Society for Sexual Medicine Pre‐congress Penile Prosthesis hands‐on workshop. The workshop included 4 h of lectures and 2 h of hands‐on cadaveric laboratory experience using three‐piece inflatable penile prosthesis. The Shapiro–Wilk test was used on self‐rated procedural confidence levels, which proved the normality. A non‐parametric McNemar test was used to examine the change in the number of correct answers. Results: Of those who attended the cadaver laboratory, just 45 who answered the survey both before and after the workshop were included for analysis. Significant objective improvements were noted in procedural knowledge test scores (44.30 ± 0.027 vs 72.44 ± 0.024, P  < 0.05) and median surgical confidence levels (4 vs 3 and 2, P  < 0.001) of the urologists after the completion of the workshop. Conclusions: Cadaveric hands‐on workshop training improves urologists' procedural knowledge and surgical confidence levels in carrying out three‐piece inflatable penile prosthesis surgery. The feasibility of such workshops should be considered in increasing the surgical expertise of general urologists in prosthetic urology.